Atherogenic index of plasma combined with carotid crouse score predicts coronary artery disease in young and middle-aged adults - Xi Wu; Mingxing Wu; Haobo Huang; Zhe Liu; He Huang; Lei Wang (Scientific Reports)
Abstract This retrospective study included 642 patients aged 18–59 years who underwent carotid ultrasound and coronary angiography. Patients were grouped by coronary artery disease (CAD) status and median Gensini score. Clinical characteristics, the atherogenic index of plasma (AIP), and carotid Crouse scores were compared. Multivariate logistic regression analysis was performed to identify independent predictors of CAD and severe coronary stenosis. Receiver operating characteristic (ROC) curve analyses assessed the diagnostic performance of AIP, Crouse score, and their combination. Both AIP and Crouse score were significantly higher in CAD patients compared to non-CAD controls (P < 0.001) and in high versus low Gensini score groups (P < 0.001). Multivariate analyses identified AIP (odds ratio [OR] = 1.219 for CAD; OR = 1.575 for severe stenosis) and Crouse score (OR = 1.543 for CAD; OR = 1.253 for severe stenosis) as independent predictors. ROC curve analysis revealed that the combined model had higher area under the curve (AUC) values for predicting CAD (AUC = 0.700) and severe coronary stenosis (AUC = 0.754) compared to either AIP or Crouse score alone. Both the AIP and carotid Crouse score are independent predictors of CAD presence and severity. Their combined use significantly improves diagnostic performance, offering a practical, non-invasive strategy for early CAD screening and risk stratification in this population.